Identification of parameters that predict sport climbing performance - Sanchez, X.; Torregrossa, M.; Woodman, T.; Jones, G.; Llewellyn, D. J. (Frontiers in Psychology, 2019)
In recent years, extreme sport-related pursuits including climbing have emerged not only as recreational activities but as competitive sports. Today, sport climbing is a rapidly developing, competitive sport included in the 2020 Olympic Games official program. Given recent developments, the understanding of which factors may influence actual climbing performance becomes critical. The present study aimed at identifying key performance parameters as perceived by experts in predicting actual lead sport climbing performance. Ten male (Mage = 28, SD = 6.6 years) expert climbers (7a+ to 8b on-sight French Rating Scale of Difficulty), who were also registered as climbing coaches, participated in semi-structured interviews. Participants` responses were subjected to inductive-deductive content analysis. Several performance parameters were identified: passing cruxes, strength and conditioning aspects, interaction with the environment, possessing a good climbing movement repertoire, risk management, route management, mental balance, peer communication, and route preview. Route previewing emerged as critical when it comes to preparing and planning ascents, both cognitively and physically. That is, when optimizing decision making in relation to progressing on the route (ascent strategy forecasting) and when enhancing strategic management in relation to the effort exerted on the route (ascent effort forecasting). Participants described how such planning for the ascent allows them to: select an accurate and comprehensive movement repertoire relative to the specific demands of the route and reject ineffective movements; optimize effective movements; and link different movements upward. As the sport of climbing continues to develop, our findings provide a basis for further research that shall examine further how, each of these performance parameters identified, can most effectively be enhanced and optimized to influence performance positively. In addition, the present study provides a comprehensive view of parameters to consider when planning, designing and delivering holistic and coherent training programs aimed at enhancing climbing performance.